The effect of feeding live yeast and yeast extracts on growth performance and antimicrobial susceptibility of fecal Escherichia coli in sows and nursery pigs - Chance, Jenna Austin (Kansas State University, 2021)
This thesis is comprised of 3 chapters involving studies evaluating live yeast and yeast extracts with or without the addition of pharmacological levels of Zn, feeding sows live yeast and a yeast extract and following their offspring into the nursery where progeny were fed varying inclusions of yeast additives and direct fed microbials (DFM). Chapter 1 involved 360 weanling barrows to determine the effects of feeding live yeast and yeast extracts with or without pharmacological Zn on nursery pig growth performance, fecal dry matter (DM), and antimicrobial susceptibilities of fecal E.coli. The results suggest that feeding pharmacological Zn for 21-d post-weaning is an effective strategy to optimize growth performance, economic criteria, and increase fecal DM for the first few days following weaning. Although all isolates were classified as susceptible to ciprofloxacin, the minimal inhibitory concentration (MIC) of fecal E.coli tended to be increased when pigs were fed pharmacological levels of Zn but no difference was observed to the remaining thirteen antimicrobials that were evaluated. Thus, the short-term use of pharmacological levels of Zn did not increase antimicrobial resistance (AMR). There was no benefit for any of the growth, economic, fecal DM, or AMR response criteria when live yeast and yeast extracts were included in the diets. Chapter 2 involved three batch-farrowing groups where 80 sows were used to determine the effects of feeding live yeast and a yeast extract’s impact on sow and litter performance. One of the three sow groups (27 sows) were used to determine the yeast additives impact on the antimicrobial susceptibility of sow fecal E.coli. The results suggest that feeding live yeast and a yeast extract, from d 110 of gestation through lactation, may increase sow feed intake but had no impact on any other sow or litter performance criteria. A diet by sampling day interaction revealed that fecal E.coli isolates gained resistance to the antimicrobial cefoxitin over time when the yeast additives were included in the diet, but the main effect of diet had no impact on any of the fourteen antibiotics tested. Chapter 3 consisted of two experiments which used 670 weaned pigs to evaluate previous sow treatment (control vs yeast additives) and nursery diets with varying combinations of yeast additives and DFM. In Exp. 1, subsequent offspring from one of the sow groups in chapter 2 were fed either a control diet or a diet that contained live yeast and yeast extracts to evaluate growth performance and the AMR patterns of fecal E.coli. In Exp 2., subsequent offspring from one of the sow groups in chapter 2 were fed either a control diet, a diet containing yeast extracts (DFM 1), or a diet with Bacillus spp. and yeast extracts (DFM 2). Results from both studies suggest that feeding sows yeast additives from d 110 of gestation through lactation can improve growth performance of their offspring in the nursery. In Exp. 1, feeding live yeast and yeast extracts in the nursery appeared to hinder growth performance. However, in Exp. 2, pigs that were fed DFM 2 reported optimized growth in the late nursery period. In Exp 1., results suggest that progeny from sows that were fed yeast might increase the potential of fecal E.coli MIC to nalidixic acid, ciprofloxacin, and gentamicin. Yet, feeding live yeast and yeast extracts in the nursery may lower the MIC of azithromycin and chloramphenicol of fecal E.coli.
Keywords: Antimicrobial resistance; Growth; Live yeast probiotic; Nursery pigs; Sows; Yeast extracts